The impact of COVID-19 on PRO development, collection and implementation: views of UK and Ireland professionals - Patricia Holch; Grace Turner; Anju D Keetharuth; E Gibbons; Kim Cocks; Kate L Absolom (SpringerOpen, 2023)
Abstract Background PROs are valuable tools in clinical care to capture patients' perspectives of their health, symptoms and quality of life. However the COVID-19 pandemic has had profound impacts on all aspects of life, in particular healthcare and research. This study explores the views of UK and Irish health professionals, third sector and pharmaceutical industry representatives and academic researchers on the impact of COVID-19 on PRO collection, use and development in clinical practice. Methods A volunteer sample took part in a 10 question cross sectional qualitative survey, on the impact of COVID-19, administered online via Qualtrics. Demographic data was descriptively analysed, and the qualitative free text response data was subject to thematic analysis and summarised within the Strengths, Weaknesses, Opportunities and Threats (SWOT) framework. Results Forty nine participants took part located in a range of UK settings and professions. Participants highlighted staff strengths during the pandemic including colleagues' flexibility and ability to work collaboratively and the adoption of novel communication tools. Weaknesses were a lack of staff capacity to continue or start PRO projects and insufficient digital infrastructure to continue studies online. Opportunities included the added interest in PROs as useful outcomes, the value of electronic PROs for staff and patients particularly in relation to integration into systems and the electronic patient records. However, these opportunities came with an understanding that digital exclusion may be an issue for patient groups. Threats identified included that the majority of PRO research was stopped or delayed and funding streams were cut. Conclusions Although most PRO research was on hold during the pandemic, the consensus from participants was that PROs as meaningful outcomes were valued more than ever. From the opportunities afforded by the pandemic the development of electronic PROs and their integration into electronic patient record systems and clinical practice could be a lasting legacy from the COVID-19 pandemic.